EFEKTIVITAS PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DAN RESPON SISWA - Uswatun Hasanah Hasibuan; Eva Yanti Siregar; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The aims of the research is to describe online learning effectiveness on pandemic Covid-19 period in terms of mathematic problem solving ability and students’ response at the eighth grade students of SMP Negeri 4 Padangsidimpuan. The approach of the research used quantitative descriptive and 15 students as the subject of the research. Questionnaire and test were used in collecting the data. Analysis statistics shows a) the average of online learning on pandemic Covid-19 period is 76.33 (good category), b) the average of mathematic problem solving ability is 38.70 (poor category), and c) the average of students’ response is 62.83 9 enough category). Furthermore, based on inferential statistics by using pair sample ttest ( SPSS 22) shows the significant value is less than 0.005 ( 0.000<0.05). It’s concluded online learning effectiveness on pandemic Covid-19 period in terms of mathematic problem solving ability and students’ response at the eighth grade students of SMP Negeri 4 Padangsidimpuan.